(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
This work reported the results of copper content in the soil profiles of three different aged cocoa plantations subjected to copper- fungicide application and the various vegetational components (pod, beans, leaves, trunk bark, lateral root and twig). Soil copper at various depth considered ranged from 5.0 -42.0 μgg-1. Copper contents in both fresh and dry leaves of cocoa and banana were consistently high in all the three plantations. The copper contents ranged from 56-300μgg-1 (dry wt.) in cocoa trunk bark and 86-161μgg-1 in banana trunk bark. There was evidence of age-dependent accumulation of copper in cocoa pod and beans; hence it can be used to assess the degree of copper contamination. Copper contents from roots ranged from 408-2, 203μgg-1 (dry wt.). The soil did not appear contaminated by copper but alternative fungicide is recommended since copper accumulation in the cocoa beans was evident. Bangladesh J. Sci. Ind. Res. 41(3-4), 129-140, 2006